2013
DOI: 10.1021/jp407769s
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transport Limitations of Redox Mediators in Dye-Sensitized Solar Cells: Investigation Based on a Quasi-Linear Model

Abstract: A simplified reaction−diffusion model is proposed to show the origins of inefficient charge transport in dye-sensitized solar cells (DSCs) based on bulky complex redox shuttles. In this model, diffusion length of the oxidized species in electrolyte solution is defined and assumed to depend on the average density of the conduction band electrons. The resulting quasi-linear equations enable the density profiles of electrons and redox shuttles to be calculated directly. When the charge transport of a DSC is under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Thereby, the results of J sc are not influenced by the diffusion limitation of cobalt complexes. Otherwise, the J sc – I 0 plot should be curved in event of inefficient mass transport of redox shuttles . Thus, it is concluded that the employment of J sc in place of U inj in eq could give reasonable estimation for the steady-state lifetime.…”
Section: Resultsmentioning
confidence: 99%
“…Thereby, the results of J sc are not influenced by the diffusion limitation of cobalt complexes. Otherwise, the J sc – I 0 plot should be curved in event of inefficient mass transport of redox shuttles . Thus, it is concluded that the employment of J sc in place of U inj in eq could give reasonable estimation for the steady-state lifetime.…”
Section: Resultsmentioning
confidence: 99%
“…These equations were solved numerically in one dimension by using Clark-Nicolsen method. In these numerical calculations, we applied reflective boundary conditions for n c , el ox , and [26]. At the contact between TiO 2 film and TCO sheet (x=0), the interfacial density of the conduction band electron (n 0 c ) is related to its Fermi-level (E 0 F,n ).…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Since reported by O'Regan and Gratzel in 1991, dye-sensitized solar cells (DSSCs) have attracted growing interests as important alternatives to conventional silicon-based solar cells due to low cost, simple fabrication process, and high energy conversion efficiency. [1][2][3][4][5][6] In general, a DSSC is composed of three main components including a dye-sensitized photoanode, an electrolyte containing a redox couple such as iodide/triiodide (I À / I 3 À ), and a counter electrode. The photoanode can be made of a thin layer of transparent conducting oxide (TCO) on a glass substrate, and the TCO layer is typically coated with a porous lm of semiconductor nanoparticles (e.g., the nanoparticles of anatase-phase TiO 2 ).…”
Section: Introductionmentioning
confidence: 99%